Learn Azure in a Month of Lunches, 2E, video edition - Foulds, Iain; Foulds, Iain (Manning Publications, 2020)
A great overview of the vast Azure offerings--from the essentials to the good stuff. Juraj Borza, NIKÉ You can be incredibly productive with Azure without mastering every feature, function, and service. Learn Azure in a Month of Lunches, Second Edition gets you up and running quickly, teaching you the most important concepts and tasks in 21 practical bite-sized lessons. As you explore the examples, exercises, and labs, you'll pick up valuable skills immediately and take your first steps to Azure mastery! This fully revised new edition covers core changes to the Azure UI, new Azure features, Azure containers, and the upgraded Azure Kubernetes Service. about the technology Microsoft Azure is vast and powerful, offering virtual servers, application templates, and prebuilt services for everything from data storage to AI. To navigate it all, you need a trustworthy guide. In this book, Microsoft engineer and Azure trainer Iain Foulds focuses on core skills for creating cloud-based applications. about the book Learn Azure in a Month of Lunches, Second Edition , is a tutorial on writing, deploying, and running applications in Azure. In it, you'll work through 21 short lessons that give you real-world experience. Each lesson includes a hands-on lab so you can try out and lock in your new skills. what's inside Understanding Azure beyond point-and-click Securing applications and data Automating your environment Azure services for machine learning, containers, and more about the audience This book is for readers who can write and deploy simple web or client/server applications. about the author Iain Foulds is an engineer and senior content developer with Microsoft. The author presents Azure in exactly the right order so the reader can put all the pieces together easily and logically. George Onofrei, DevEx Solutions A lifesaver if you want or have to dive into Azure. Charles Lam, EVN AG Iain Foulds's book gives you a head start in Azure without a big-time commitment. Peter Kreyenhop, Department of Internal Affairs (NZ) NARRATED BY DEREK LETTMAN.